2018
DOI: 10.1186/s12916-018-1189-1
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain charts for different body mass index groups for women in Europe, North America, and Oceania

Abstract: BackgroundGestational weight gain differs according to pre-pregnancy body mass index and is related to the risks of adverse maternal and child health outcomes. Gestational weight gain charts for women in different pre-pregnancy body mass index groups enable identification of women and offspring at risk for adverse health outcomes. We aimed to construct gestational weight gain reference charts for underweight, normal weight, overweight, and grades 1, 2 and 3 obese women and to compare these charts with those ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 34 publications
3
91
1
4
Order By: Relevance
“…However, a large systematic review showed that reporting error did not bias associations between pregnancy‐related weight and birth outcomes . We used maternal pre‐pregnancy BMI‐specific weight gain for gestational age z ‐scores, which classify weight gain independently of gestational age . This approach allows assessment of the unbiased associations between gestational weight gain and pregnancy outcomes that are highly correlated with gestational age at birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a large systematic review showed that reporting error did not bias associations between pregnancy‐related weight and birth outcomes . We used maternal pre‐pregnancy BMI‐specific weight gain for gestational age z ‐scores, which classify weight gain independently of gestational age . This approach allows assessment of the unbiased associations between gestational weight gain and pregnancy outcomes that are highly correlated with gestational age at birth.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated maternal pre‐pregnancy BMI‐specific weight gain for gestational age z ‐scores based on reference charts created using data from this collaboration (Supporting Information Appendix S1). These z ‐scores were categorised into six categories [<−2.0 standard deviation (SD), −2.0 to −1.1 SD, −1.0 to −0.1 SD, 0–0.9 SD, 1.0–1.9 SD and ≥2.0 SD) and into low (≤−1.1 SD), medium (−1.0 to 0.9 SD) and high (≥1.0 SD) weight gain.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-pregnancy nutritional status versus maternal weight gain and neonatal size Similar tendencies have been observed also in other regions of the world. In the USA, excess weight gain was reported for 50% of all pregnant women [8,12], and as many as 64-66% for women with pre-pregnancy overweight or obesity [6,19]. Weight gain below recommendations was found in 20% of the subjects [12].…”
Section: Nomentioning
confidence: 99%
“…The maximum recommended weight gain for obese women is 7 kg lower than for women with normal BMI. For that reason, most sources report that the percentage of women with pre-pregnancy obesity/ overweight whose weight gain during pregnancy is above recommendations -even despite lower weight gain in kilograms -is higher than the percentage of women with normal pre-pregnancy BMI but excess gestational weight gain [1,19,33].…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation